Pengaruh Revitalisasi Pasar Terhadap Aktivitas Perdagangan Di Pasar Jongke Kecamatan Laweyan Kota Surakarta - Rivai, Fandy Ahmad; , Drs. M. Musyiam, M. TP (2017)
This research was conducted with the aim to analyze market conditions before and after Jongke revitalization and revitalizing influence against trading activities. This research uses the methods of survey and in-depth interview in the market Jongke with the technique of sampling Stratified Random Sampling with Proportional criteria have been defined for the respondent merchant with 106 total sample of respondents consisted of merchant stalls, 28 42 36 los, and merchant traders oprokan. As for buyers using the technique of Aksidental with a total of 106 samples of respondents. Based on the results of the study can note that: (1) the physical condition of the market jongke in the form of building walls, floors and parking area are having a pretty good changes including wall and renovated most of the building, the floor is ceramic tile and already partially leveled with casted, as well as increased parking area. Broad market before the revitalization of 5000m2 while after revitalizing 12.253 m2. Each spacious stall experienced an expansion of 2m2, los 4m2, as well as expansion of experience oprokan experienced an expansion of 2m2. The location of the traders before the revitalization not set appropriate group. After revitalizing layout of merchants already divided properly i.e. the merchant stalls are located on the front side of the market and the East side, merchants are on the middle section of the los, los are traders on the back of the market, and traders were at the front of the bike to the East. Electricity market before the revitalization of less power, less bright, and dues are not proportional to the electrical facilities are accepted. Whereas after revitalizing power bigger, brighter and dues of electricity per month. The cleanliness and security of the market there are no security guards and a janitor just dump every two days. While there is already a revitalization after a security guard stand every morning and afternoon as well as a janitor throw away trash twice a day. A means of revitalizing the market before there are no counters, there is only 1 bathroom and 1 TOILET. After revitalization on the front counter of the market as well as the addition of bathroom and WC units. (2) providing a revitalizing effect on trading activity, i.e. with increasing income traders and the type of merchandise.